International travel and the elite athlete - Pipe, A. L. (Clinical Journal of Sport Medicine, 2011)
International travel is a frequent occurrence in the life of the elite athlete; such travel can pose challenges to the sport medicine practitioner. Travel is also the reality of many recreational level or subelite athletes as opportunities for international competition and training proliferate. An appreciation of the range of responsibilities associated with the preparation for and the strategies to facilitate such travel is essential for any physician charged with the care of athletes and teams. An appreciation of (1) the medical and public health challenges associated with competition in a particular setting; (2) the requirements for vaccination and immunization; (3) the strategies for the management of jet lag and climatic or environmental extremes; (4) the range of supplies and equipment necessary for travel to certain locales; (5) the need to ensure the availability of ample familiar and nutritious foods; (6) the potential need for specialty care in strange settings; (7) the management of common travel-associated illness; and (8) the challenges associated with the evacuation of an injured athlete are fundamental to the successful management of international travel involving athletes and teams. The adoption of a methodical approach to pre-trip planning can ensure an enhanced travel experience, illness-free training and competition, and facilitate optimal performance.